SEBARAN SPASIAL WILAYAH RAWAN KEKERINGAN LAHAN TANAMAN PADI SEBAGAI UPAYA MANAJEMEN RISIKO BENCANA KEKERINGAN DI PROVINSI JAWA TIMUR - Yosafat Doni Haryanto; Noval Ariefrohman Budiprabowo (Republic of Indonesia Defense University, 2022)
Drought is one of the events which cause a lot of negative impact on the region, the area of agriculture drought can reduce yield and cause crop failure. East Java province is one of the largest contributors to the national rice production in Indonesia. Increased agricultural production can be done with risk management with a variety of drought mitigation strategies and disaster relief efforts preventive. One such effort is to make early control planning using drought-prone maps. Based on data analysis and processing of the obtained results that the distribution of drought in East Java province when the dry season, is very vulnerable category almost dominates the region's peak in August to October. Entering the rainy season spreading drought began to decrease, but the coastal areas are still in a very vulnerable category. The characteristics of the region is very vulnerable category during the year were in Sampang, Pamekasan, Sumenep, Tulungagung and part of the north coast of East Java Province which has the least rainfall than other areas and the climate is very dry. The movement patterns prone to drought from January to May, with a category extremely prone generally around the north coast of East Java Province, entered the month of June to November the drought extends further into the center of East Java Province, then in December the level of dryness safely started having additional area amid Province East Java. Risk management drought in East Java province, especially for areas prone and extremely vulnerable to the need for the regulation of early warning system for extreme climatic (ENSO), which affects drought, local legislation to establish the scale of priorities for the use dn water management, preparation of hazard maps of drought, determination anticipatory technology (manufacture ponds, weather modification technology, alternative energy sources, adjustment of cropping and cultivation technology) and irrigation systems adapted to climate forecasting, development of reward and punishment system for the people who do the conservation and rehabilitation of water and land resources.